2017
DOI: 10.1007/s11010-017-3024-y
|View full text |Cite
|
Sign up to set email alerts
|

HUCMNCs protect vascular endothelium and prevent ISR after endovascular interventional therapy for vascular diseases in T2DM rabbits

Abstract: The therapeutic effect of transplantation of human umbilical cord blood cell-derived mononuclear cells (HUCMNCs) on treating in-stent restenosis (ISR) after endovascular interventional therapy (EIT) was evaluated in preclinical rabbit model of type 2 diabetes mellitus (T2DM)-related peripheral artery disease (PAD). HUCMNCs were transplanted to T2DM rabbits subjected to femoral artery occlusion surgery and received EIT. Serum concentration of soluble vascular endothelial cadherin (VE-cad) and plasma concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The injured vascular endothelium can cause vascular inflammation, which accelerates lipid deposition and thrombosis. These changes contribute to neointimal hyperplasia and in-stent restenosis (ISR) [3,4]. The use of drug-eluting stents (DESs) inhibits neointimal hyperplasia but also inhibits reendothelialisation.…”
Section: Introductionmentioning
confidence: 99%
“…The injured vascular endothelium can cause vascular inflammation, which accelerates lipid deposition and thrombosis. These changes contribute to neointimal hyperplasia and in-stent restenosis (ISR) [3,4]. The use of drug-eluting stents (DESs) inhibits neointimal hyperplasia but also inhibits reendothelialisation.…”
Section: Introductionmentioning
confidence: 99%
“…The primary targets of hyperglycemia appear to be the endothelial cells, which may induce endothelial dysfunction and accelerate vasculopathy [1,2]. In an experimental animal model with type 2 diabetes mellitus (T2DM), the remarkable improvement of vascular endothelial function hold promise as therapeutic approaches to decrease the risk of cardiovascular diseases [3,4]. Altered endothelial phenotype is a prominent feature of metabolic disturbance in DM.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, how to reduce the restenosis after surgery and keep the target vessel unobstructed in the long term is a clinical problem to be solved urgently. Our research reported that combined with umbilical cord blood stem cell transplantation after intervention could protect vascular endothelial damage and prevent restenosis after intervention 8,9 . It is also found that excimer laser ablation technique was safer in clinical operation and could also be used for subendothelial opening 10 .…”
Section: Introductionmentioning
confidence: 77%
“…Our research reported that combined with umbilical cord blood stem cell transplantation after intervention could protect vascular endothelial damage and prevent restenosis after intervention. 8,9 It is also found that excimer laser ablation technique was safer in clinical operation and could also be used for subendothelial opening. 10 With the development of interventional devices, drug-loaded devices will become the mainstream technology to reduce restenosis after intervention.…”
Section: Introductionmentioning
confidence: 99%